Atomic layer deposited V2O5 coatings: a promising cathode for Li-ion batteries - Martyn Pemble (Journal of Electrochemical Science and Engineering, 2019)
A modified, thermal atomic layer deposition process was employed for the pulsed chemical vapor deposition growth of vanadium pentoxide films using tetrakis (dimethylamino) vanadium and water as a co-reagent.Depositions were carried out at 350oC for 400 pulsed CVD cycles, and samples were subsequently annealed for 1hour at 400°C in air to form materials with enhanced cycling stability during the continuous lithium-ion intercalation/deintercalation processes. The diffusion coefficient was estimated to be 2.04x10-10 and 4.10x10-10 cm2 s-1 for the cathodic and anodic processes, respectively. These values are comparable or lower than those reported in the literature, indicating the capability of Li+ of getting access into the vanadium pentoxide framework at a fast rate. Overall, it presents a specific discharge capacity of 280 mAh g-1, capacity retention of 75 % after 10000 scans, a coulombic efficiency of 100 % for the first scan, dropping to 85 % for the 10000th scan, and specific energy of 523 Wh g-1.